2020
DOI: 10.1111/oik.06871
|View full text |Cite
|
Sign up to set email alerts
|

The role of preadaptation, propagule pressure and competition in the colonization of new habitats

Abstract: To successfully colonize new habitats, organisms not only need to gain access to it, they also need to cope with the selective pressures imposed by the local biotic and abiotic conditions. The number of immigrants, the preadaptation to the local habitat and the presence of competitors are important factors determining the success of colonization. Here, using two experimental set‐ups, we studied the effect of interspecific competition in combination with propagule pressure and preadaptation on the colonization … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 68 publications
8
39
0
Order By: Relevance
“…This might offset some of the maladaptation and the priority effect advantage enjoyed by native species (Chase, 2003). Such interaction of traits and propagule pressure is in line with recent evidence from field and laboratory experiments (Alzate et al, 2020; Kempel et al, 2013). Still, propagule pressure alone does not explain why invasives also manage the fourth phase, landscape spread.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This might offset some of the maladaptation and the priority effect advantage enjoyed by native species (Chase, 2003). Such interaction of traits and propagule pressure is in line with recent evidence from field and laboratory experiments (Alzate et al, 2020; Kempel et al, 2013). Still, propagule pressure alone does not explain why invasives also manage the fourth phase, landscape spread.…”
Section: Discussionsupporting
confidence: 88%
“…However, previous experimental studies focused mainly on the earlier stages of invasion and thus, generalized insights that include landscape spread are still missing (cf. Alzate, Onstein, Etienne, & Bonte, 2020; Kempel, Chrobock, Fischer, Rohr, & van Kleunen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the belt, an invasive NNS was, on average, four times as abundant as a non-invasive NNS (with species abundance measured as the number of records). Several studies have already demonstrated the crucial role of propagule pressure, and especially the number of new immigrants, on the colonization success of NNS (Cassey et al, 2018;Alzate et al, 2020). The higher abundance of invasive NNS in the belts could thus result in a higher propagule pressure inside PAs, and a subsequent higher probability of establishment of invasive NNS in PAs.…”
Section: Factorsmentioning
confidence: 99%
“…Under neutral expectations, endemic taxa that randomly increase in abundance are more likely to persist longer, and thus extant old residents as a whole should be more abundant than recent colonizers (Rosindell & Phillimore, 2011). However, immigration pressure and pre‐adaptation of colonizing species might counteract interspecific competition in the new environment (Alzate, Onstein, Etienne, & Bonte, 2020), and might have the potential to reverse neutral expectations on the abundance of endemics and colonizing taxa. Predator and parasite release of new colonizers or the concurrent introduction of new parasites to local specialists may also be alternative explanations for the apparent success of new colonizing over resident species (Ricklefs, 2010).…”
Section: Figurementioning
confidence: 99%